Case report: administration of immune checkpoint inhibitor for SMARCB1 (INI1)-negative rhabdoid carcinoma with microsatellite instability (MSI)-high in the right colon - Toshinori Kobayashi; Yuki Matsui; Hisanori Miki; Masahiko Hatta; Mitsuaki Ishida; Hironaga Satake; Mitsugu Sekimoto (Surgical Case Reports)
Abstract Background Malignant tumors with rhabdoid features are rare, highly aggressive, and some of them are characterized by SMARCB1 (INI1) loss. Although cases of rhabdoid carcinoma are extremely rare, its occurrence in the colon has been reported previously. Case presentation A 71-year-old Japanese female patient presented with loss of appetite, fatigue, and weight loss. Computed tomography demonstrated a tumor in the right colon that infiltrated the surrounding kidneys and swelling of the left supraclavicular and periaortic lymph nodes. Laparotomy revealed that the tumor was unresectable because it had directly invaded the head of the pancreas and duodenum. Therefore, ileocecal vascularized bulky lymph nodes were sampled, and gastrojejunostomy with Braun’s anastomosis and ileotransversostomy were performed as palliative procedures. Histopathological examination of the lymph nodes revealed that the neoplastic cells had rich eosinophilic cytoplasm and eccentrically located large nuclei characteristic of rhabdoid carcinoma. In addition, these neoplastic cells lacked SMARCB1 expression; therefore, the patient was diagnosed with SMARCB1-negative rhabdoid carcinoma. The postoperative course was uneventful. Molecular analysis confirmed that the neoplastic cells had high microsatellite instability (MSI); therefore, two cycles of pembrolizumab were administered. However, no clinical benefit was noted, and the patient died 3 months postoperatively. Conclusion This is the first report of a case of SMARCB1-negative rhabdoid colon carcinoma with high MSI treated with pembrolizumab. Rhabdoid carcinoma is highly aggressive; therefore, additional studies are required to determine the therapeutic strategy for SMARCB1-negative rhabdoid colorectal carcinoma.